The Impact of Urbanization on the Annual Average Temperature of the Past 60 Years in Beijing. (21st May 2014) - Wang, Yong; Ji, Wei; Yu, Xinfang; Xu, Xinliang; Jiang, Dong; Wang, Zhangang; Zhuang, Dafang
Abstract : Global warming, which is representatively caused by CO2 -based greenhouse gases, has caused widespread concern in the global scientific community and gets the high attention of each government in the world. Human activities impact climate change through greenhouse gas emissions and land use changes. The current study on the impact of urbanization on the annual average temperature of the recent 60 years in Beijing was conducted using 1951–2012 temperature data. Anomaly analysis, quadratic polynomial trend method, and moving average method were employed to indicate the temporal variation of temperature. The results showed that average temperature increased both in urban and rural areas. The temperature of urban Beijing increased during the period from 1951 to 2012, especially from 1971 to 1994. The temperature of rural Beijing showed a faster increase than that of the urban area from 1989 to 1998. However, the rate of temperature increase slowed down in recent years. This type of change was temporally consistent with the process of land use change and urbanization in Beijing. Economic restructuring and improvement of urban planning may have been one of the reasons that the regional warming has been slowed down in the rural area.